2017
DOI: 10.1016/j.pmedr.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Adherence support strategies for exercise interventions in people with mild cognitive impairment and dementia: A systematic review

Abstract: Exercise-based therapy may improve health status for people with Mild Cognitive Impairment (MCI) or dementia but cannot work without adherence, which has proven difficult. This review aimed to evaluate strategies to support adherence among people with MCI or Dementia and was completed in Nottingham/UK in 2017. A narrative synthesis was used to investigate the effectiveness or usefulness of adherence support strategies. Fifteen adherence support strategies were used including theoretical underpinning (programme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 31 publications
5
74
0
Order By: Relevance
“…Studies in patients with acute brain injury, dementia, and serious mental illness support the efficacy and feasibility of exercise despite cognitive issues. [49][50][51] Although thrombocytopenia is not considered a contraindication to exercise, in keeping with data in stem cell transplant patients, 52 exercises with high risk of injury or falling should be avoided, especially if platelets are <20,000/ll.…”
Section: Cirrhosis-related Safety Considerationsmentioning
confidence: 93%
“…Studies in patients with acute brain injury, dementia, and serious mental illness support the efficacy and feasibility of exercise despite cognitive issues. [49][50][51] Although thrombocytopenia is not considered a contraindication to exercise, in keeping with data in stem cell transplant patients, 52 exercises with high risk of injury or falling should be avoided, especially if platelets are <20,000/ll.…”
Section: Cirrhosis-related Safety Considerationsmentioning
confidence: 93%
“…Empirical data gathered in exercise intervention studies with people with dementia give preliminary support to the relevance of some of the constructs identified in the original version of the PHYT-in-dementia. For example, a recent review of the literature [25] has found that higher motivation to adhere to an intervention programme is linked to certain intervention characteristics, including the use of behaviour change techniques (e.g., motivational interviewing), the provision of tailored supervision/activities to meet participants' individual needs, the setting of SMART (i.e., specific, measurable, attainable, realistic, time-bound) goals, and the use of booklets/guidance on how to do the exercises. The construct "carer's characteristics" has also proved relevant in relation to motivation to exercise in people with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise and physical activity have multiple benefits in people with mild cognitive impairment (MCI) or dementia including positive effects on functional abilities, mood, mobility and cognition (Forbes, 2015;Brett, Traynor, & Stapley, 2016;Rao, Chou, Bursley, Smulofsky, & Jezequel, 2014;Barreto, 2015;Bossers et al, 2014;Hernandez, 2015). Three recent systematic reviews (van Alphen, Hortobagyi, & van Heuvelen, 2016;van der Wardt et al, 2017;Nyman, Adamczewska, & Howlett, 2018) identified barriers and facilitators for exercise and physical activity engagement in people with dementia. In addition to practical support strategies such as exercise recording sheets, reminders and pedometers, the reviews identified intra-and interpersonal factors that might support exercise and physical activity engagement in people with dementia.…”
Section: Introductionmentioning
confidence: 99%